2020
DOI: 10.1186/s12872-020-01374-8
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression profile and its potential regulative role in human abdominal aortic aneurysm

Abstract: Background: This study aimed to identify the differentially expressed circular RNAs (circRNAs) between human abdominal aortic aneurysm (AAA) and the control group. Methods: High-throughput sequencing was applied to determine the circRNA expression profiles of 4 paired aortic samples. Real-time quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was carried out to testify 6 randomly selected dysregulated circRNAs. Kyoto Encyclopedia of Genes and Genomes and Gene ontology (GO) analysis were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Moreover, differentially expressed circRNAs were discovered in both mice and human with abdominal aortic aneurysm (AAA) 48,49 . Specially, circCCDC66 was upregulated in AAA 48 .…”
Section: Mechanisms Of Circrnas In the Occurrence And Development Of mentioning
confidence: 99%
“…Moreover, differentially expressed circRNAs were discovered in both mice and human with abdominal aortic aneurysm (AAA) 48,49 . Specially, circCCDC66 was upregulated in AAA 48 .…”
Section: Mechanisms Of Circrnas In the Occurrence And Development Of mentioning
confidence: 99%
“…First, appropriate public datasets of human AAA were collected by using Gene Expression Omnibus (GEO) database in National Center of Biotechnology Information (http://www.ncbi.nlm.nih.gov/geo/). Overall, three microarray datasets (GSE7084, GSE57691 and GSE144431) were included in the present study (Table SI) (17)(18)(19). In GSE7084, seven AAA samples and eight healthy samples were involved for mRNA expression profiles by GPL2507 platform.…”
Section: Methodsmentioning
confidence: 99%
“…However, the functional role(s) of these circRNAs in AAA development in animal models and their therapeutic potential are yet to be elucidated. [83]. Finally, a total of 411 differentially expressed circRNAs were detected in AAA samples, including 145 upregulated cir-cRNAs and 266 downregulated circRNAs.…”
Section: Verified Circrnas In Aaasmentioning
confidence: 99%
“…Zhou et al from China observed differential expression of circRNAs in AAA samples and controls, so they subsequently conducted high-throughput sequencing to determine the circRNA expression patterns in four pairs of aortic samples, including four consecutive AAA cases undergoing open surgery and four brain-dead heart-beating organ samples [ 83 ]. Finally, a total of 411 differentially expressed circRNAs were detected in AAA samples, including 145 upregulated circRNAs and 266 downregulated circRNAs.…”
Section: Verified Circrnas In Aaasmentioning
confidence: 99%